2017
DOI: 10.1021/jacs.7b06338
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Azide–Alkyne Cycloaddition To Access 1,5-Disubstituted 1,2,3-Triazoles in Air and Water

Abstract: Transition-metal-catalyzed or metal-free azide-alkyne cycloadditions are methods to access 1,4- or 1,5-disubstituted 1,2,3-triazoles. Although the copper-catalyzed cycloaddition to access 1,4-disubstituted products has been applied to biomolecular reaction systems, the azide-alkyne cycloaddition to access the complementary 1,5-regioisomers under aqueous and ambient conditions remains a challenge due to limited substrate scope or moisture-/air-sensitive catalysts. Herein, we report a method to access 1,5-disubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 49 publications
1
72
0
Order By: Relevance
“…A) Generalschemeo f the Huisgen reaction and CuAAC. [28] Initial investigationsi nto the NiAAC were performed by treating benzyl azide and phenylacetylene with a nickel catalysta tr oom temperature withoutadegassing step. C) Synthesis of the 1,5-disubstituted 1,2,3-triazole ring by using ar uthenium catalyst.…”
Section: Recent Trends In Metal-based Click Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A) Generalschemeo f the Huisgen reaction and CuAAC. [28] Initial investigationsi nto the NiAAC were performed by treating benzyl azide and phenylacetylene with a nickel catalysta tr oom temperature withoutadegassing step. C) Synthesis of the 1,5-disubstituted 1,2,3-triazole ring by using ar uthenium catalyst.…”
Section: Recent Trends In Metal-based Click Reactionsmentioning
confidence: 99%
“…In 2017, Hong et al reported nickel-catalyzed azide-alkyne cycloaddition (NiAAC; Scheme 8D). [28] Initial investigationsi nto the NiAAC were performed by treating benzyl azide and phenylacetylene with a nickel catalysta tr oom temperature withoutadegassing step. Interestingly,i nt he absence of the nickelocene (Cp 2 Ni)o rb identate Xantphos ligand, the reaction for the formation of 1,2,3-triazole was not successful.…”
Section: Recent Trends In Metal-based Click Reactionsmentioning
confidence: 99%
“…To develop applicable approaches allowing the selective synthesis of 1,5‐disubstituted 1,2,3‐triazoles, huge endeavors have been devoted. In this regard, the synthesis employing the catalysis of transition metal species such as iridium, ruthenium, nickel have been disclosed. The rare earth samarium has also been found as practical catalyst in catalyzing the synthesis of 1,5‐disubstituted 1,2,3‐triazoles .…”
Section: Introductionmentioning
confidence: 99%
“…Thus the ideal CuAAC is considered as click reaction and widely used in organic chemistry, medicinal chemistry, material chemistry and chemical biology. [5] For internal alkynes, Fokin found that the CuAAC is applicable for 1-iodoalkynes, and Micouin revealed that aluminum acetylide is also compatible in this process (Scheme 1C). [4] Recently, Hong and coworkers established a similar reaction using Cp 2 Ni/Xantphos as catalyst, and this process is compatible with water and air.…”
mentioning
confidence: 99%
“…[4] Recently, Hong and coworkers established a similar reaction using Cp 2 Ni/Xantphos as catalyst, and this process is compatible with water and air. [5] For internal alkynes, Fokin found that the CuAAC is applicable for 1-iodoalkynes, and Micouin revealed that aluminum acetylide is also compatible in this process (Scheme 1C). [6,7] In 2014, Jia and Sun developed an iridium-catalyzed regioselective cycloaddition of azides and internal thioalkynes.…”
mentioning
confidence: 99%